From scandal to reform: approaches to research integrity at a turning point - Felicitas Hesselmann; Martin Reinhart (Journal of Responsible Innovation)
This perspective article explores the historical evolution of scandals related to academic integrity and their implications for the relationship between science and politics. We argue that there are three distinctive waves of scandalization since the postwar era: The first wave, starting in the 1970s, led to governance measures addressing public trust issues in science funding. The 1980s and 1990s witnessed a second wave centered on research misconduct, prompting the establishment of boundary organizations such as the Office of Research Integrity. Since the 2010s, the third wave shifted focus to concerns such as Open Science and reproducibility, giving rise to a mainly intra-scientific moral entrepreneurship that unfolds not along one-time scandals anymore, but as part of a continuous crisis discourse. This current wave of reform movements is met with considerably less intra-scientific resistance than its predecessors and hence may inadvertently achieve regulatory goals surpassing previous political intentions.